A profile on parotid surgeries - K. S., Gangadhara; Bhat, Amrutha V.; S., Sridhara (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: A study of the various parotid swellings that underwent surgery in a tertiary care hospital was conducted. Different parameters like preoperative investigations including fine needle aspiration cytology (FNAC) and radiological investigations, modified aesthetic incision, type of surgery and outcome following surgery were assessed. Methods: This was a prospective institutional based study. A total of 19 cases of parotid swellings were considered. A new aesthetically acceptable incision was used in all patients. Post operatively, facial nerve and other complications were assessed. A comparison between FNAC diagnosis and histopathology diagnosis was made. Results: The FNAC and histopathological examination results were same in 15 of the 19 cases considered. All patients were followed up for a period of 6 months and the post-operative scar was well accepted by all patients. Conclusions: Pleomorphic adenoma, one of the most common causes of parotid swelling, is well diagnosed by FNAC. Ultrasonography is a useful tool to diagnose benign parotid tumours. The modified incision used gives an imperceptible scar post operatively.